2013
DOI: 10.1186/cc13092
|View full text |Cite
|
Sign up to set email alerts
|

High fat feeding promotes obesity and renal inflammation and protects against post cardiopulmonary bypass acute kidney injury in swine

Abstract: IntroductionObesity confers a survival advantage in the critically ill and in patients undergoing cardiac surgery. We explored whether an obesogenic high fat diet could confer protection against post cardiopulmonary bypass (CPB) acute kidney injury (AKI) in a swine model.MethodsIn this study, 28 anaesthetised adult female Landrace White swine (55 to 70 kg) were allocated into a 4 group design to either 2.5 hours of CPB or Sham operation with or without pre-procedural high fat (HF) feeding containing 15% lard, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 45 publications
5
22
0
1
Order By: Relevance
“…However, AKI mortality in our study followed a reversed J shape, indicating that although obese people had an increased mortality risk compared to overweigh patients, their mortality incidence was still lower than for underweight and normal-weight cases, which is similar to the results from a previous report about mortality in nondialyzed advanced chronic kidney disease male patients [32]. The data indicated that in contrast to RRT, obesity was a survival advantage for AKI patients, which supports findings of Sleeman et al [33], according to which obesity had beneficial effects on kidneys by inducing renal inflammation in a CPB swine model.…”
Section: Discussionsupporting
confidence: 91%
“…However, AKI mortality in our study followed a reversed J shape, indicating that although obese people had an increased mortality risk compared to overweigh patients, their mortality incidence was still lower than for underweight and normal-weight cases, which is similar to the results from a previous report about mortality in nondialyzed advanced chronic kidney disease male patients [32]. The data indicated that in contrast to RRT, obesity was a survival advantage for AKI patients, which supports findings of Sleeman et al [33], according to which obesity had beneficial effects on kidneys by inducing renal inflammation in a CPB swine model.…”
Section: Discussionsupporting
confidence: 91%
“…This study showed that HFD-supplementation could not impress renal function in renal injury induced by kidney I/R, however this regimen elevated body weight, energy intake and lee index. Although it was indicated that HFD leads to kidney histopathlogical changes, inflammation, oxidative stress (5,20,21) and aggravated kidney I/R induced renal injury (22), one study in parallel with our study reported that HFD for 12 weeks developed overweight and did not affect kidney function and maintained renal blood flow and glomerular filtration rate (GFR), and inhibited kidney injury after cardio bypass surgery (23). The effect of HFD for 2 weeks before surgery indicated no more damage in outcome than normal diet against I/R injury (24).…”
Section: Conclusion: the Effect Of Hfd On Renal I/rsupporting
confidence: 47%
“…A limitation of our study is that this model only reflects less severe AKI; the changes n renal clearance that we have described equate to the ‘Risk’ stage of the RIFLE classification, now considered as Stage 1 AKI in the recent Kidney Diseases Improving Global Outcomes consensus definition [ 25 ]. Animal recovery with re-evaluation at 24 hours is a key component, and strength of the current model as our previous studies have shown that changes in filtration immediately post CPB are not indicative of later pathophysiology [ 26 , 27 ]. However reproducible recovery mandates that the nature of the injury sustained by study subjects is less severe.…”
Section: Discussionmentioning
confidence: 99%